Fasting Management and Its Relationship with Health According to Islam - Nur, Zainuddin; Malik, Abdul (Economic: Journal Economic and Business, 2022)
Fasting is the fourth pillar of Islam. An order from Allah SWT and Rasulullah SAW that must be carried out by believers, both mandatory (Ramadan fasting) and sunnah (sunnah fasting).  The ultimate goal of fasting is to gain the pleasure of Allah SWT by first bearing the title of piety.  In addition to the predicate of piety, fasting also has many health benefits. But what is no less important than the purpose of fasting is the problem of mastering knowledge and how we carry out the fast.  Therefore, the author has completed this paper with a valid postulate of fasting, fasting management and the health benefits of fasting according to management science